2014
DOI: 10.1111/disa.12072
|View full text |Cite
|
Sign up to set email alerts
|

The tsunami's impact on mortality in a town severely damaged by the 2011 Great East Japan Earthquake

Abstract: This study identifies the relationship between tsunami damage and mortality through a demographic pyramid of a town severely damaged by the tsunami following the Great East Japan Earthquake of 11 March 2011. It uses cross-sectional data collection. Volunteers visited all households, including shelters, and asked residents about the whereabouts of family members and neighbours. The information was collated with lists of evacuees and the dead to confirm the whereabouts of all residents about 50 days after the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…The municipalities were divided into three groups for inter-regional comparison: (1) 15 municipalities in Fukushima that were severely impacted by the tsunami ("15 Fukushima municipalities"), (2) municipalities in Fukushima other than those mentioned in (1) and municipalities in the Miyagi and Iwate prefectures that neighbor Fukushima ("nearby municipalities"), and (3) municipalities in other prefectures ("other municipalities").…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The municipalities were divided into three groups for inter-regional comparison: (1) 15 municipalities in Fukushima that were severely impacted by the tsunami ("15 Fukushima municipalities"), (2) municipalities in Fukushima other than those mentioned in (1) and municipalities in the Miyagi and Iwate prefectures that neighbor Fukushima ("nearby municipalities"), and (3) municipalities in other prefectures ("other municipalities").…”
Section: Datamentioning
confidence: 99%
“…Disasters cause numerous casualties [1][2][3] and negatively impact the survivors [4,5]. Previous studies indicated that besides direct injuries in the disaster, there is an increase of acute stress, depression, and heart disease [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…With the development of disaster warning and technology for prediction, the impact intensity and approximate paths of some disasters, such as typhoon, can be predicted to a certain extent. Such prediction can be used to designate the size, paths and ways of shunting of medical surge in the early warning phase after a disaster to avoid massive attack of medical surge peaks . From Wenchuan earthquake to Yushu earthquake in China, the principle of medical evacuation tended to be ‘early evacuation, all evacuation’; evacuation levels were gradually simplified.…”
Section: Responsementioning
confidence: 99%
“…Such prediction can be used to designate the size, paths and ways of shunting of medical surge in the early warning phase after a disaster to avoid massive attack of medical surge peaks. 16 From Wenchuan earthquake to Yushu earthquake in China, the principle of medical evacuation tended to be 'early evacuation, all evacuation'; evacuation levels were gradually simplified. Casualties were evacuated directly from affected areas to rear hospitals through highways and railways, or in some cases mainly through air evacuation; triage became less prominent, whereas special treatment was required as soon as possible.…”
Section: Shunt Of Catastrophic Medical Surgementioning
confidence: 99%
“…Older people were particularly vulnerable to death or injury in the disaster. According to research conducted in the town of Otsuchi immediately after the tsunami, 1,412 older people-8.8 per cent of the total population-were killed or went missing; 60.2 per cent of them were aged 65 and over, and 37.5 per cent were aged 75 and over (Nagata et al, 2014). The meltdown, explosions, and radioactive release at the nuclear power plant in Fukushima, an unprecedented event in Japan, greatly complicated and extended the recovery process.…”
Section: Introductionmentioning
confidence: 99%